2023
DOI: 10.1186/s12302-023-00738-z
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of lignite post-mining landscapes under changing environmental conditions: what can we learn from a comparison between the Rhenish and Lusatian region in Germany?

Abstract: Background The decision of the German federal government to cease lignite mining until 2038 or—if possible—already earlier until 2030, will cause manifold transition processes in the remaining lignite mining districts of Germany. The two largest districts are located in geographically opposite regions: The Rhineland in the western part and Lusatia in the east of Germany. As particularly these two mining districts will experience severe changes in their socioeconomic as well environmental condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…However, it is equally important to ensure that these incentives are aligned with environmental sustainability objectives. According to the literature, one of the key principles after mine closure is the long-term sustainability of the land and ecosystem, which requires the provision of services that exclude environmental pollution (Gerwin et al 2023). Practices that promote the use of renewable energy sources, sustainable primary production through 'smart agriculture', and the creation of energy communities should be integrated within these incentives (Marinakis et al 2020;Majeed et al 2023) This study revealed that European and domestic financial instruments are necessary to support sustainable entrepreneurship, create quality jobs, and upgrade the knowledge and skills of the workforce to enter the green labor market.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is equally important to ensure that these incentives are aligned with environmental sustainability objectives. According to the literature, one of the key principles after mine closure is the long-term sustainability of the land and ecosystem, which requires the provision of services that exclude environmental pollution (Gerwin et al 2023). Practices that promote the use of renewable energy sources, sustainable primary production through 'smart agriculture', and the creation of energy communities should be integrated within these incentives (Marinakis et al 2020;Majeed et al 2023) This study revealed that European and domestic financial instruments are necessary to support sustainable entrepreneurship, create quality jobs, and upgrade the knowledge and skills of the workforce to enter the green labor market.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the location of eastern Germany, the climate water balance (CWB) is mostly low, necessitating high IWD (Drastig et al, 2016). The majority of the IWD in summer is met by groundwater pumping, leading to a lowering of the water table, and increasing competing demands and pressure from other sectors like public water supply (Gerwin et al, 2023;Mirschel et al, 2019) and ecological demands.…”
Section: Deficit Irrigation Water Demand Estimationmentioning
confidence: 99%
“…Negative CWB shows the possibility of high IWD, thus the need for irrigation. Gerwin et al (2023) noted that high IWD in the summer leads to a decrease in groundwater levels and an increase in competition between agriculture and public water supply. They also stressed the need for an optimized irrigation system to cushion these impacts (Gerwin et al, 2023).…”
Section: Mean Seasonal Water Balance Of Maize and Potatomentioning
confidence: 99%
See 1 more Smart Citation
“…Gerwin at al. 1 draw attention to the decrease in groundwater levels in the western brown coal mining district in the Rhineland, the largest brown coal mining area in Europe, which has affected an approximately 4400 km2 area 2,3 . Similar issues arise in other mining regions in Germany, such as in the Lusatia region 4 .…”
Section: Introductionmentioning
confidence: 99%